DEVELOPMENT AND VALIDATION OF ULTRAVIOLET–VISIBLE SPECTROPHOTOMETRIC METHOD FOR ESTIMATION OF GLYCYRRHIZIN IN METHANOLIC EXTRACT OF GLYCYRRHIZA GLABRA L - HYDER, IMRAN; NASEER, ARIF; AHMAD, ADIL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The pure form of glycyrrhizin was bought from Yucca Enterprises, Mumbai-37, India. The pure form of drug used in treatment of acne vulgaris disease. Pharmacognostical studies of Glycyrrhiza glabra L. indicated surprising antibacterial action against Propionibacterium acnes. Methods: A simple, rapid, accurate, precise, and economic spectrophotometric technique for estimation of glycyrrhizin in methanolic extract of G. glabra L. have been developed. Glycyrrhizin exhibit absorbance most at 254 nm when phosphate buffer (pH-6.8) methanol is used as solvent in 70:30 proportion, so absorbance was once measured at the identical wave lengths for the determination of glycyrrhizin. Glycyrrhizin obeys the Beer Lambert’s law in the concentration range of 4–24 μg/ml. Results: This method was validated according to International Council for Harmonization guidelines and can be adopted for the general analysis of glycyrrhizin in hydroalcoholic extract of G. glabra. The approach is simple, rapid, safe, accurate, affordable, and beneficial for standardization of the licorice products. Conclusion: The results applied in the routine analysis and quality control of pharmaceutical dosage forms containing glycyrrhizin.